Indonesian Medicinal Plants for Anticancer - Syazili Mustofa (Journal of Pharmaceutical and Natural Resources, 2025)
The potential of Indonesia's natural wealth of plants to be developed as anticancer agents is enormous, thanks to its abundant biodiversity. Indonesia has become a "natural laboratory" with various plants traditionally used for treatment, including cancer, by local communities. This potential is supported by several primary factors: extensive biodiversity, bioactive compound content, and empirical use in traditional medicine. Several studies have identified several Indonesian plants that show potential as anticancer agents: Tapak Dara (Vinca rosea), Taxol (Taxus sp), Lempuyang Wangi (Zingiber zerumbet), Temu Kunci (Boesenbergia pandurata), Melinjo/Tangkil (Gnetum gnemon), Soursop leaves (Annona muricata), Cloves (Syzygium aromaticum), and Typhonium flagelliforme (Typhonium flagelliforme). Despite its great potential, developing anticancer drugs from Indonesian plants faces several challenges: scientific proof, standardization, high research and development costs, and regulatory and patent aspects. To address these challenges, a comprehensive development strategy is needed, including: Enhancing collaboration between research institutions, universities, the pharmaceutical industry, and the government; Conducting ethnobotanical studies to document traditional knowledge of medicinal plants; Developing standardized herbal formulas (phytopharmaceutics) that have supporting scientific data; Strengthening basic research to identify and test specific bioactive compounds; and Encouraging innovation in the extraction and purification of active compounds.